Assessing the Rate, Natural History, and Treatment Trends of Intracranial Aneurysms in Patients with Cranial Dural Arteriovenous Fistulae (dAVF); A CONDOR Investigation. (16th November 2020) - Abecassis, Isaac J; Meyer, R. Michael; Levitt, Michael R; Sheehan, Jason P; Chen, Ching-Jen; Gross, Bradley A; Lockerman, Ashley; Fox, W. Christopher; Giordan, Enrico; Lanzino, Giuseppe; Starke, Robert M; Chen, Stephanie H; et al.
Abstract: INTRODUCTION: Aneurysms associated with brain arteriovenous malformations (AVMs) and Moya-Moya disease represent a distinct pathology compared to saccular aneurysms, including higher rupture risk and spontaneous resolution after AVM treatment. Multiple series report an elevated risk of associated aneurysm in cranial dural arteriovenous fistula (dAVF) ranging from 13-21%. However, the natural history, rate of spontaneous regression, and ideal treatment regimen are not well-characterized. METHODS: The CONsortium for Dural arteriovenous fistula Outcomes Research (CONDOR) data from 16 centers was retrospectively reviewed. Analysis was performed comparing patients with only dAVF to those with dAVF and aneurysm (dAVF+). Patient demographics, dAVF information, aneurysm information, and follow-up data were collected. RESULTS: Of the 1, 077 patients in CONDOR, 968 (93.2%) had only dAVF, while 71 (6.8%) had dAVF+. dAVF+ patients had higher rates of hypertension (53.5% vs. 40.2%, p = 0.033) and smoking (46.5% vs. 28.3%, p = 0.002). Fourteen (19.7%) dAVF+ patients presented with aneurysmal rupture, and 1 (1.4%) ruptured during follow-up. Patients with dAVF+ were more likely to have dAVF located at non-conventional locations, less likely to have arterial supply to dAVF from external carotid artery branches, and more likely to have supply from internal carotid artery pial branches. Rates of cortical venous drainage and Borden grade were comparable between groups. A minority (19.7%) of aneurysms were "flow related" (located on an arterial pedicle to the dAVF) Most underwent treatment either via endovascular (39.4%) or microsurgical (14.1%) techniques; a subset observed either with or without dAVF treatment spontaneously regressed (7%). CONCLUSION: Patients with dAVF have an elevated risk of harboring a concomitant intracranial aneurysm (6.8%) compared to the general population (∼2 8 -5 9 %). Patients with dAVF+ have differences in fistula angioarchitecture. A subset of dAVF+ patients harbor aneurysms that are flow related, and may regress with dAVF treatment.